Pengelolaan Pembelajaran Seni Rupa Berbasis Budaya Lokal Di SMK Negeri 9 Surakarta - SUGESTIADI, WIDI EKO, Prof. Dr. Bambang Sumardjoko, Dr. Sabar Narimo, M.M., M.Pd (2015)
The purpose of this study was to describe (1) planning; (2) interaction; and (3) evaluation of visual arts-based subjects in the local culture SMKN 9 Surakarta The research is a qualitative research. The technique of collecting data through observation, interviews and documentation. The results showed that (1) Planning study visual arts at SMK 9 Surakarta done by preparing a teacher administration in the form of lesson plans, materials, methods, space and instructional media. Learning system using the system block that is in the tenth grade is taught the art of music, theater arts class XI and XII class art. (2) The interaction of visual arts-based learning local culture in SMKN 9 Surakarta was active and occurs from various directions. Interaction occurs between teachers and students and between students and other students. (3) The initial starting of greetings, prayers and continued apperception. Core activities are focused on four (4) it is observing activity, identify analyze and create a masterpiece. Cover the activities carried out by giving a conclusion followed by a closing prayer and greetings. (3) Assessment in the visual arts-based learning local culture in SMKN 9 Surakarta done by direct assessment test, a written test and a practical test. Assessment is carried out also by assessing the students' work. By using local culture-based learning with a system of block interesting and motivation and increased student achievement so that all students have been able to reach a value of mastery learning.